STRATEGI KOMUNIKASI KELOMPOK DALAM MEMOTIVASI BELAJAR SISWA SMP YAYASAN PENDIDIKAN SHAFIYYATUL AMALIYYAH MEDAN - Lestari, Indah (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
This study aims to find out how the group communication strategy in motivating students learning at Shafiyyatul Amaliyyah Middle School Medan. The research method used in this research is analytical descriptive which provides as detailed data as possible and then analyzes it in the form of written words. This study is included in the qualitative category, with the location of the study conducted at the Shafiyyatul Amaliyyah Education Foundation Medan Jl. Setia Budi No.191 Medan. source of data in research obtained through literature review literature. Then the source of the data came from the results of in-depth interviews with informants namely VIII-C Middle School students, Principal of Shafiyyatul Amaliyyah Middle School, then a number of Shafiyyatul Amaliyyah Middle School teachers were added. The results of this study illustrate the strategies used in group communication using the active learning approach through problem-solving methods in the hope that students can learn actively by solving problems in their lessons while researchers are only instructors to solve problems so as to create intelligence, knowledge, personality, noble character and the skills to live independently. Communication Planning conducted by Shafiyyatul Amaliyyah Middle School Teachers, namely face to face communication, is used if they expect the effect of behavior change from the communicant, because it is more persuasive and uses media communication (mediated communication), is used more for informative communication by reaching out to more communicants but very weak in terms of persuasion. The implementation of group communication conducted by Shafiyyatul Amaliyyah Middle School Teachers is, In this case, the teacher uses the Group Investigation method, where this method involves students since planning, both in determining the topic and the way to learn it through investigation.